2003
DOI: 10.1001/archneur.60.11.1625
|View full text |Cite
|
Sign up to set email alerts
|

A Korean Kindred With Autosomal Dominant Nocturnal Frontal Lobe Epilepsy and Mental Retardation

Abstract: Disorders associated with mutations in the transmembrane region 2 of CHRNA4 are genetically and phenotypically heterogeneous. Distinctive features of this kindred include (1) mental retardation in all affected members available for testing, (2) abnormal brain findings on fluorodeoxyglucose F 18 with positron emission tomography, (3) poor response to carbamazepine, and (4) full penetrance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 24 publications
(19 reference statements)
2
35
2
2
Order By: Relevance
“…This variability may be family, and thus presumably nAChR gene mutation, dependent. Cho and colleagues described a different family with ADNFLE (CHRNA4 mutation) and markedly impaired general intellectual skills [33]. Similarly, we found that severe ADNFLE can be associated with marked psychiatric disability and intellectual impairment [34].…”
Section: Discussionsupporting
confidence: 65%
“…This variability may be family, and thus presumably nAChR gene mutation, dependent. Cho and colleagues described a different family with ADNFLE (CHRNA4 mutation) and markedly impaired general intellectual skills [33]. Similarly, we found that severe ADNFLE can be associated with marked psychiatric disability and intellectual impairment [34].…”
Section: Discussionsupporting
confidence: 65%
“…Affected individuals typically present without adverse neurological symptoms other than seizures, although several reports describe ADNFLE patients with a concomitant history of psychiatric problems (4,5), cognitive deficits (3), or mental retardation (6). Clinical features of ADNFLE include clusters of brief seizures that initiate during non-rapid eye movement (NREM) sleep.…”
mentioning
confidence: 99%
“…Whereas the frontal lobe origin, adolescent onset, and clusters of nocturnal, hyperkinetic motor seizures are signatures of this disorder, the ADNFLE seizure phenotype shows incomplete penetrance and can present with (6,8) or without (4, 9) intra-and interfamilial variation in expressivity.…”
mentioning
confidence: 99%
“…[16][17][18][19] It has been assumed that founder effect is not relevant to ADNFLE, because most of the families studied come from different countries, 20 and a previous haplotype study of the Australian and Norwegian family 14 showed no genetic connection.…”
Section: Introductionmentioning
confidence: 99%
“…11 Among the four mutations in CHRNA4 (Ser280Phe, Ser284Leu, Leu291dup and Thr293Ile), Ser280Phe and Ser284Leu have been identified in several unrelated families (mutation names may be different from those of previous papers; we use NP_000735.1): the Ser280Phe in an Australian, Spanish, Norwegian and Scottish families, [12][13][14][15] and the Ser284Leu in a Japanese, Korean, Polish and Lebanese families. [16][17][18][19] It has been assumed that founder effect is not relevant to ADNFLE, because most of the families studied come from different countries, 20 and a previous haplotype study of the Australian and Norwegian family 14 showed no genetic connection.…”
Section: Introductionmentioning
confidence: 99%